1986
DOI: 10.1093/bja/58.suppl_1.32s
|View full text |Cite
|
Sign up to set email alerts
|

Use of Atracurium in Neonatal Anaesthesia

Abstract: Atracurium was administered to neonatal patients on 270 occasions without any difficulties being encountered. More detailed observations in 60 patients showed that, in 16 neonates 3 days of age and older, with a core temperature greater than 36 degrees C, the standard dose of atracurium 500 micrograms kg-1 had a mean duration of clinical effect of 23.1 +/- 3.4 min--the shortest in any group of children so far studied in Liverpool. In only three of the 16 was antagonism of residual neuromuscular blockade consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 5 publications
2
10
0
Order By: Relevance
“…Atracurium and cisatracurium have the advantage that degradation occurs by Hofmann elimination at body temperature and pH; the offset of action is therefore largely independent of hepatic and renal function (89). However, in the patient with normal liver function, most of the dose is cleared by liver esterases (90,91). Similar to vecuronium, satisfactory conditions for intubation are achieved within 90 s and the duration of action is classed as short to intermediate, with a range of 15–40 min.…”
Section: Neuromuscular Blockersmentioning
confidence: 99%
See 1 more Smart Citation
“…Atracurium and cisatracurium have the advantage that degradation occurs by Hofmann elimination at body temperature and pH; the offset of action is therefore largely independent of hepatic and renal function (89). However, in the patient with normal liver function, most of the dose is cleared by liver esterases (90,91). Similar to vecuronium, satisfactory conditions for intubation are achieved within 90 s and the duration of action is classed as short to intermediate, with a range of 15–40 min.…”
Section: Neuromuscular Blockersmentioning
confidence: 99%
“…Cisatracurium, an isomer of atracurium, is not associated with histamine release but there are very few available data in neonates. The recommended dose of atracurium is 0.5 mg·kg –1 (90,91).…”
Section: Neuromuscular Blockersmentioning
confidence: 99%
“…Most muscle relaxants have not been formally licensed for use in the newborn infant. Although not licensed for use in neonates, atracurium has been reported to be of benefit as long ago as 1986 (4). Atracurium is used in a number of UK neonatal units as medication for intubation (5).…”
Section: Cases 3–6mentioning
confidence: 99%
“…Atracurium is used in a number of UK neonatal units as medication for intubation (5). Previous groups have suggested that neonates are more sensitive to atracurium than infants and also that a lower body temperature may increase sensitivity (4,6,7).…”
Section: Cases 3–6mentioning
confidence: 99%
“…Pharmacokinetic studies have shown that below the usual therapeutic dose (0.5 mg/kg for pediatric patients and 0.6 mg/kg for adult patients), atracurium produces maximum neuromuscular blocking effect 3-5 min following injection, and recovery is generally 95% complete 1 h postinjection [9,12,24,25]. High doses of atracurium tend to prolong the duration of action and increase the risk of adverse reactions such as cardiovascular collapse and seizure activity [14,23]. The toxic level that leads to circulatory depression and seizure activity has been well established in animals [4,13,15,28], but it remains unclear in humans.…”
Section: Introductionmentioning
confidence: 99%